PREVALENCE OF VALVULAR HEART DISEASE IN CHRONIC KIDNEY DISEASE PATIENTS ON MAINTENANCE HEMODIALYSIS (The Research of Medical Science Review, 2025)
Objective: To determine the Prevalence of Valvular Heart Disease in Chronic Kidney Disease Patients on Maintenance Hemodialysis Study design: Descriptive Longitudinal study Place and duration of study: Department of Nephrology in collaboration with the Department of Cardiology, Liaquat University Hospital, Hyderabad from 13-9-2024 to 13-3-2025. Methodology: This study included 89 consecutive patients with end stage renal disease of either gender of more than 18 years who were initiated maintenance hemodialysis for at least last three months due to any cause, twice per week. On dialysis free day, patients’ blood sample were taken to assess the hemoglobin, albumin, phosphorus and calcium level and subjected for Echocardiography. Disease was deemed as positive by presence of Mitral regurgitation or/ and Aortic valve regurgitation lesion. All collected data was analyzed using the SPSS-26 software. The quantitative variables were reported through means and standard deviations. For the qualitative variables, percentages and frequencies were computed. To evaluate the impact of effect modifiers on VHD, the chi-square/fisher exact test was utilized. A P-value of less than 0.05 was considered significant. Results: The study revealed that among 89 patients of ESRD, 45 (50.5%) were male and 44 (49.5%) were female with mean age 53.492 ±16.35 years and duration of dialysis was 8.76 + 2.56 months. Valvular heart disease was found in 60 (67.4%) cases of ESRD who were undergoing maintenance hemodialysis. Mitral regurgitation found in 35 (39.3%) cases, Aortic valve regurgitation in 15 (16.8%) cases and both were found in 10 (11.2%) cases. Conclusion: The high prevalence of VHD has been found in current study. Therefore, we may draw the conclusion that CVD is the leading cause of mortality among ESRD patients, causing a strikingly high burden and posing a unique therapeutic challenge. The severity and risk of developing VHD are directly correlated with the length of hemodialysis and ESRD.